Best practices of promoting a positive school learning climate among principals of high performing secondary schools towards realization of Education Blueprint 2013-2025 Malaysia - Salleh, Mohamad Johdi; Hatta, Muhammad (2016)
The purpose of the study was to investigate the best practices of promoting a positive school learning climate among principals of High Performing Secondary Schools Malaysia according to principals’ and teachers’ perceptions. The Principal Instructional Management Rating Scale (PIMRS) modified by Hallinger and Murphy (1985), Latip (2006), Hatta (2010), Surayya (2016) was used as the data collection instrument through survey questionnaire. There were 871 respondents of different genders, ethnics, type of schools, and, position of responsibilities at schools were participated. The result of the study shows that the highest score was on dimensions ‘Developing and Enforcing Academic Standards’ with mean 4.290 and standard deviation 0.814. It was respectively followed by ‘Providing Incentives for Learning’ mean 4.060 and standard deviation 0.904; ‘Protecting Instructional Time’ mean 3.855 and standard deviation 0.963 and ‘Providing Incentives for Teachers’ mean 3.607 and standard deviation 1.095. Meanwhile, the two best items practiced by the principals was ‘Use assemblies to honor students for their academic work and/or behavior in classroom’ mean 4.39 and ‘Encourage teachers to start class on time and teach to the end of the period’ mean 4.38. It is hoped that this study will provide useful findings which will effectively assist the process of promoting a positive school learning climate among principals and teachers of secondary schools in Malaysia. Consequently, facilitate and improve students' academic performance in achieving the first class human capital who are compatibly excellent nationally and internationally as stipulated in the purpose of establishing the high performance schools by the Ministry of Education Malaysia towards realization of Vision 2020 and the Education Development Plan 2013-2025.